Penyebaran Informasi Melalui Desain Komunikatif di Halaman Facebook (International Forum of Researchers and Lecturers, 2024)
Information is something that has a very high level of interest information in life. In line with the advancement of information and communication technology, new media has been created as an aspect of interaction and communication. In the process of communicating and disseminating information to the public, the internet becomes an indispensable thing. The reason is, the internet has an interesting program in the form of social media as a tool to spread information to the public. Facebook is one of the social media that people are interested in communicating and disseminating information. Facebook's social media provides a variety of feature options, such as status, photo and video sharing, user-created content. Status, photos, and videos features are commonly used to disseminate information. This form of information dissemination can be a digital design that includes graphic design, illustrations and communicative explanations. A communicative design is a design created to convey information. Where communicative design is absolutely necessary to disseminate information to the public. Communicative design contains valid, interesting, concise information but the information delivered remains easy to understand and clear. That's why information dissemination is well received by the public. This research aims to understand how communicative design should be used to optimize information dissemination on Facebook platforms and its impact on user responses to messages delivered to the Community.